Genetic modifiers of the intermediate phenotypes in sickle cell anemia - Aguiar, Laura (2017)
Sickle cell anemia (SCA) is an inherited blood disorder characterized by the presence of hemoglobin S (HbS). This disease is caused by a single point mutation in the beta-globin gene with a corresponding amino acid substitution at the sixth position of the beta-globin chain. Vaso-occlusion and hemolytic anemia are the major features of this disease, however, SCA patients present clinical and hematologic variability that cannot be only explained by the single mutation. Others genetic modifiers and environmental factors are important for the clinical phenotype. We studied the association between several hematological and biochemical parameters and a set of genetic variants in 26 pediatric SCA patients. Myeloperoxidase (MPO) and placental growth factor (PlGF) were determined by ELISA (R&D Systems Inc.). Amplification of DNA samples for the rs1050829 characterization, in the glucose-6-phosphate dehydrogenase (G6PD) gene, was performed by PCR followed by restriction fragment length analysis. A multiplex PCR assay was used for simultaneous amplification of glutathione S-transferases mu (GSTM1) and theta (GSTT1). All statistical tests were performed with SPSS 24.0 software. Our results show higher levels of MPO (p<0.001) and PlGF (p=0.048) in SCA patients, compared with healthy adult controls. Moreover, in these patients we found associations between: 1) lower levels of total hemoglobin and the GSTM1 null genotype (p=0.044); 2) higher levels of HbS with the rs1050829_G genotype (hemizygous males) in the G6PD gene (p=0.026). We suggest that the mentioned polymorphisms in GSTM1 and G6PD genes may act as genetic modifiers in SCA, which could be useful for the prediction of increased susceptibility to complications. Furthermore, our results reinforce the importance to study biochemical parameters for a better understanding of the clinical outcome of this disease.